Perlindungan Hukum Bagi Pekerja Kontrak Yang Mengalami Pemutusan Hubungan Kerja Pada Masa Kontrak (Studi Kasus Putusan Nomor : 82/Pdt.Sus-Phi/2016/PN. Mdn) - Sintha Dewi Silalahi; Zaini Munawir; Muhammad Yusrizal Adi Syaputra (Universitas Medan Area, 2019)
Work relationships that occur between companies are reciprocal relationships, i.e. relationships that need each other. The company will not be able to carry out its activities without having workers and vice versa. Individuals who work in a company certainly work to get a wage. Based on this relationship, each party, namely the company and workers, is protected by their rights and obligations. This type of normative juridical research is carried out by reviewing various formal legal rules such as laws, regulations and literature containing theoretical concepts which are then linked to the issues to be discussed. Data analysis is done by qualitative analysis, namely by interpreting the symptoms that occur, not in exposure to behavior, but in a tendency. The working relationship between the Plaintiff and the Defendant is in fact not fulfilling the requirements as described, namely a permanent work relationship, because the conditions that are not fulfilled so that the employment relationship between the Plaintiff and the Defendant must be interpreted as non-permanent work. The working relationship between the Plaintiff and the Defendant which is not permanent, then by itself can be the basis of the working relationship between the Plaintiff and the Defendant is made working relations based on the Specific Time Work Agreement (PKWT)